PEMBUATAN SUSU TEMPE KURMA SEBAGAI ALTERNATIF MINUMAN KESEHATAN - U.Yuyun Triastuti; Sa’roni (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Dates milk tempe is an alternative drink for health, which is made from tempe extract with natural sweetener honey and enriched with dates, so it is safe and healthy for consumption by all ages. The research objectives were to determine: 1) the organoleptic quality of date palm tempe milk; 2) community acceptance of date palm tempe milk; 3) determine the content of carbohydrates, protein and fat. The research method of making date palm milk is carried out in accordance with the procedure for making tempe milk. Organoleptic tests to determine acceptance were carried out on 30 semi-trained and untrained panelists. The nutritional content of date palm tempeh is calculated using the Gizipro application. The results showed that date palm milk has sensory characteristics of sweet and savory taste, aroma of soybean tempeh and dates, thick texture and dark brown color. Contains 5.31 g carbohydrates; 0.11 g protein; 0.14 g fat; and 2.14 mg of calcium. It has low carbohydrates, low fat content compared to tempeh milk, so it can be drunk by all ages and can prevent degenerative diseases.